Predictive value of prognostic nutritional and systemic immune-inflammation indices for patients with microsatellite instability-high metastatic colorectal cancer receiving immunotherapy - Yi, Jiahong; Xue, Ju; Yang, Lin; Xia, Liangping; He, Wenzhuo (Frontiers in Nutrition, 2023)
Abstract Background: The prognostic nutritional index (PNI) and systemic immune-inflammation index (SII) are indicators of nutritional immune status. They have been reported associated with clinical outcomes of various solid tumors. However, it is unclear whether they can serve as predictors for patients with microsatellite instability-high (MSI-H) metastatic colorectal cancer (mCRC) receiving immunotherapy. Our objective was to study the prognostic value of PNI and SII in these patients. Methods: 75 MSI-H mCRC patients were enrolled in our study. Logistic regression analysis was used to identify features that influenced immunotherapy response. Survival differences between groups of mCRC patients were compared using the Kaplan-Meier method and log-rank test. The independent risk parameters for progression-free survival (PFS) and overall survival (OS) of patients with MSI-H mCRC were established by Cox proportional risk regression analysis. Results: The optimal SII and PNI cutoff values were 409.6 and 51.35. Higher PNI (P = 0.012) and lower high-density lipoprotein cholesterol (HDLC, P = 0.012) were associated with a better immunotherapy response. SII (P = 0.031), cholesterol (CHO) (P = 0.007) and aspartate aminotransferase (AST) (P = 0.031) were independent prognostic factors correlated with OS. Higher PNI (P = 0.012) and lower AST (P = 0.049) were negative predictors of PFS. In addition, patients suffered from immune-related adverse events (irAEs) had a lower SII level (P = 0.04). Conclusion: Higher AST and SII, and lower PNI predict worse outcomes in MSI-H mCRC patients undergoing immunotherapy. Moreover, patients with lower SII before immunotherapy suffered from irAEs more often.